2016
DOI: 10.1093/nar/gkw274
|View full text |Cite
|
Sign up to set email alerts
|

The structure of ends determines the pathway choice and Mre11 nuclease dependency of DNA double-strand break repair

Abstract: The key event in the choice of repair pathways for DNA double-strand breaks (DSBs) is the initial processing of ends. Non-homologous end joining (NHEJ) involves limited processing, but homology-dependent repair (HDR) requires extensive resection of the 5′ strand. How cells decide if an end is channeled to resection or NHEJ is not well understood. We hypothesize that the structure of ends is a major determinant and tested this hypothesis with model DNA substrates in Xenopus egg extracts. While ends with normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 72 publications
4
31
0
Order By: Relevance
“…Purified proteins were aliquoted to 3 μl, frozen in liquid nitrogen and stored at –80°C. Expression and purification of wild-type (WT) MRN complex and a nuclease dead-mutant complex containing Mre11(H130N) were described previously (80,88). Expression and purification of WT RPA complex and the RPA (1NΔ) mutant complex were described previously (61).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified proteins were aliquoted to 3 μl, frozen in liquid nitrogen and stored at –80°C. Expression and purification of wild-type (WT) MRN complex and a nuclease dead-mutant complex containing Mre11(H130N) were described previously (80,88). Expression and purification of WT RPA complex and the RPA (1NΔ) mutant complex were described previously (61).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this idea, it has been shown that Sae2 and MRX are not essential for resection and downstream HR at clean DSBs in yeast (7679). In the Xenopus cytosolic extract the nuclease activity of MRN is dispensable for the overall resection of clean DSBs, which is in sharp contrast to 5′ blocked ends where the nuclease activity of MRN is absolutely essential (80). Likewise, the catalytic function of CtIP has also been shown to be dispensable for resection of clean DSBs in human cells (43).…”
Section: Introductionmentioning
confidence: 99%
“…Key factors regulating pathway choice for DSB repair are the cell cycle (116) and the nature of DNA ends (69). Whereas NHEJ-based repair pathways are active throughout the cell cycle, HR requires a DNA template for the repair and is active in only the S and G2 phases, during which the homologous sister chromosome is present.…”
Section: Mrn and Double-strand Break Repairmentioning
confidence: 99%
“…Whereas NHEJ-based repair pathways are active throughout the cell cycle, HR requires a DNA template for the repair and is active in only the S and G2 phases, during which the homologous sister chromosome is present. The nature of the DSB ends also regulates the repair pathway choice (69). If the DSB ends are free of protein adducts and damaged nucleotides, they are likely channeled through NHEJ for repair in human cells.…”
Section: Mrn and Double-strand Break Repairmentioning
confidence: 99%
“…The channeling of DSB repair intermediates to HR requires CtIP. That CtIP stimulates Mre11 endonuclease activity at DNA-protein crosslinks [17,94] suggests a mechanism for releasing Ku from DNA ends, thereby promoting resection and HR repair over DNA end protection and NHEJ repair [71,95]. …”
Section: Ctip Is a Regulatory Hub For Dsb Repair Pathway Choicementioning
confidence: 99%